(untitled) (World Economics and Finance Bulletin, 2025)
This study was aimed to demonstrate the role of internal Audit and oversight in the sustainability of higher education institutions. It also is attention to the internal auditor’s effectiveness in maintaining their sustainability and the impact of their quality of work on their achievements at all levels. The research methodology relied on a questionnaire and field visits to Wasit University, part of the Iraqi Ministry of Higher Education institutions. The results showed that internal Audit and oversight play a significant role in strengthening the decisions of the Ministry of Higher Education, but they have not been implemented effectively. Internal Audit and oversight work in the Ministry of Higher Education and its formations focuses more on monitoring financial operations (withdrawals, deposits, and annual inventory control) than on performance reports and periodic evaluations related to the academic process and making sound decisions. Internal Audit and oversight work in this institution is traditional and lacks modernity and keeping pace with developments. Therefore, a shift in internal Audit and control from traditional practices to productive, effective, and distinctive practices characterized by modernity, based on clear and transparent digital data using modern technology. This will effective and beneficial results that can be used to make sound and effective decisions that preserve the sustainability of scientific and academic work within this institution